5(5k+2)-2(4k-3)=

Simple and best practice solution for 5(5k+2)-2(4k-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(5k+2)-2(4k-3)= equation:


Simplifying
5(5k + 2) + -2(4k + -3) = 0

Reorder the terms:
5(2 + 5k) + -2(4k + -3) = 0
(2 * 5 + 5k * 5) + -2(4k + -3) = 0
(10 + 25k) + -2(4k + -3) = 0

Reorder the terms:
10 + 25k + -2(-3 + 4k) = 0
10 + 25k + (-3 * -2 + 4k * -2) = 0
10 + 25k + (6 + -8k) = 0

Reorder the terms:
10 + 6 + 25k + -8k = 0

Combine like terms: 10 + 6 = 16
16 + 25k + -8k = 0

Combine like terms: 25k + -8k = 17k
16 + 17k = 0

Solving
16 + 17k = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-16' to each side of the equation.
16 + -16 + 17k = 0 + -16

Combine like terms: 16 + -16 = 0
0 + 17k = 0 + -16
17k = 0 + -16

Combine like terms: 0 + -16 = -16
17k = -16

Divide each side by '17'.
k = -0.9411764706

Simplifying
k = -0.9411764706

See similar equations:

| 3(k-5)=5(k-9) | | 4x-26=x+31 | | 66c=u-8 | | 4n+3=6n-5 | | 3a^2-6a= | | 6=13-x | | 7x+5=12x-5 | | 7x+8-36x-9=4x+2 | | 7n-28=54 | | -6x+13=-x+8 | | 2x-12=7x-2 | | 7(4x-3)-4x=-16 | | 6q+20=19 | | -3x-15=-6 | | 3x+8+2x-3=75 | | -2(-07m+9)=4(m-7) | | 127.82=2.35h+73.77 | | 3r-2=5(r+2) | | 2(-7m+9)=4(m-7) | | 3(2x-4)=0 | | 7y+3y=9y+9 | | 12x+34=10x+200 | | 8x-3=2x+27 | | 18w-2=10-14 | | 5x+22=x+2 | | 7(-3x+5)+8=148 | | 7t-t-8=5t-4 | | 2w+6x-14y+5w+9x+8y= | | b+12-13=(b-31) | | 3(c-2)=-15 | | -1+8(n+4)=8n+31 | | x/4+1/3=x-8 |

Equations solver categories